2014
DOI: 10.1007/s10762-014-0119-3
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature grown photoconductive antennas for pulsed 1060 nm excitation: Influence of excess energy on the electron relaxation

Abstract: We investigate properties of MBE grown photoconductive terahertz (THz) antennas based on the InGaAs/InAlAs/InP material system aimed for an excitation wavelength of approx. 1060 nm. Therefore, we analyze several different approaches concerning growth parameters, layer and material compositions as well as doping. The carrier dynamics are probed via transient white-light pump-probe spectroscopy as well as THz Time Domain Spectroscopy (TDS) measurements. We find that the electron capture probability is reduced fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…One of the first solutions was to employ InGaAs/InAlAs photoconductive layers which allowed achievement of order-of-magnitude improvements versus planar antennas in terms of emission power, dark current and receiver sensitivity [31]. They were applied for continuous wave THz generation at 1.5 µm [32] optical pumping and in TDS using 1 µm wavelength excitation [33]. However, the structures were multi-layered, consisted of 100 periods InGaAs/InAlAs, and, thus, were technologically demanding and expensive for the task at hand.…”
Section: Fiber Femtosecond Laser-based Thz Sourcesmentioning
confidence: 99%
“…One of the first solutions was to employ InGaAs/InAlAs photoconductive layers which allowed achievement of order-of-magnitude improvements versus planar antennas in terms of emission power, dark current and receiver sensitivity [31]. They were applied for continuous wave THz generation at 1.5 µm [32] optical pumping and in TDS using 1 µm wavelength excitation [33]. However, the structures were multi-layered, consisted of 100 periods InGaAs/InAlAs, and, thus, were technologically demanding and expensive for the task at hand.…”
Section: Fiber Femtosecond Laser-based Thz Sourcesmentioning
confidence: 99%
“…107 Additionally, erbium arsenide (ErAs) quantum dot incorporation into the InAlAs trapping layers has been studied and shown to provide up to 1 V∕cm amplitude THz pulses at 100-mW excitation wavelength. 104 The most recent work by Dietz et al 117,118 has shown optimal growth conditions for 1060-nm excitation along with a further study of optimized Be 2þ doping for 1.55-μm excitation detectors. Over 6-THz detection bandwidth and 90-dB dynamic range was reported for detectors fabricated on InGa(Al)As multilayers with Be 2þ doping concentrations of 4 × 10 18 cm −3 .…”
Section: Indium Gallium Arsenidementioning
confidence: 98%
“…The femtosecond fiber laser pumped IPCA can be a portable and cost-effective solution to a powerful THz transceiver system. Hence, the effect of wavelengths (λ) of 800 nm (Ti:Sapphire laser), 34,35 1060 nm (Ybdoped fiber laser), 36 and 1550 nm (Er-doped fiber lasers) 37 have been studied closely. To the best of our knowledge, this is the first time, the impact of laser pulse parameters on a dense interdigitated photoconductive antenna is reported.…”
Section: Introductionmentioning
confidence: 99%